2018
DOI: 10.19030/jabr.v34i2.10135
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Political Instability Driven By The Tunisian Revolution On Stock Market Volatility: Evidence From Sectorial Indices

Abstract: The aim of this paper is to study the impact of political uncertainty, driven by the Tunisian Revolution, on return and volatility of major sectorial stock indices in the Tunisian Stock Exchange. We specifically use EGARCH (1.1) model from 01/12/2010 to 31/08/2016. This model is applied to the daily returns relevant to ten sectorial stock indices and to the Tunisian benchmark index (TUNINDEX). To test the impact of political news on returns and volatility, we divided them into two groups (good and bad news).&#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Here, the study cannot reject the second hypothesis. The result of the regression model regarding terrorism is in agreement with theoretical viewpoint and with some of the past studies (Alam, 2013;Arin et al, 2008;Bilal et al, 2012;Christofis et al, 2013;Gadhoum et al, 2017;Geyikci & Tepeci, 2017;Hadhek et al, 2019;Kollias et al, 2011;Moussa & Talbi, 2019;Nguyen & Enomoto, 2009;Zaiane, 2018) that terrorist activities create direct converse impact on investors and state business environment. However, this study results appear differently with some other studies (Arif & Suleman, 2014;Hassan et al, 2014).…”
Section: Regression Modelsupporting
confidence: 89%
See 4 more Smart Citations
“…Here, the study cannot reject the second hypothesis. The result of the regression model regarding terrorism is in agreement with theoretical viewpoint and with some of the past studies (Alam, 2013;Arin et al, 2008;Bilal et al, 2012;Christofis et al, 2013;Gadhoum et al, 2017;Geyikci & Tepeci, 2017;Hadhek et al, 2019;Kollias et al, 2011;Moussa & Talbi, 2019;Nguyen & Enomoto, 2009;Zaiane, 2018) that terrorist activities create direct converse impact on investors and state business environment. However, this study results appear differently with some other studies (Arif & Suleman, 2014;Hassan et al, 2014).…”
Section: Regression Modelsupporting
confidence: 89%
“…Besides, a study showed a strong influence of terrorism acts on the behavior of ten sectorial stock indices return to Tunisian benchmark index (TUNINDEX) using the daily data for the period (2010-2016) (Zaiane, 2018). Moreover, a study used daily data for two sub periods before and after revolution and the output shows that the terror acts affect the performance and volatility of the Tunisian market performance especially after the revolution (Moussa & Talbi, 2019).…”
Section: Terrorism and Stock Marketmentioning
confidence: 98%
See 3 more Smart Citations